Remote user supported IoT-WSN Laboratory and testbed platform: FiratWSN - Yildirim, Gungor; Tatar, Yetkin (Gazi Univ, Fac Engineering Architecture, 2019)
Along with the development of Internet of Things (IoT) and Cyber-Physical Systems (CPSs), the importance of wireless sensor networks (WSNs), which are one of their fundamental subsystems, has obviously increased. In line with this, studies towards adapting traditional WSN systems to IoT/CPS projects have gained speed. As might be expected, these types of studies require comprehensive WSN test platforms, which this process could be quite expensive and detailed. In this study, the implementation and development of a virtual WSN testbed platform, called FiratWSN, which enables the running of remote test applications for academic studies, is introduced Unlike the other similar studies in the literature, with the help of Agilla middleware, the testbed can allow a certain number of different user applications to be run concurrently on the same programmable physical WSN nodes. On the other hand, FiratWSN also includes three sub-WSNs; the FiratZigBee sub-WSN, a 1322x ZigBee sub-WSN, and an 802.15.4 sub-WSN consisting of nodes of different technologies. In this way, the testbed also provides an infrastructure for heterogeneous application tests. Users can remotely connect to the system over the internet and test their WSN applications in a flexible lab environment, which this provides an important cost and installation time saving to them.
Uzak kullanici destekli bir IoT-WSN sanal laboratuvari ve test platformu: FiratWSN
Keywords: Wireless sensor network; virtual WSN laboratory; virtualization; CoAP; Internet of things